2006
DOI: 10.1590/s0102-09352006000600029
|View full text |Cite
|
Sign up to set email alerts
|

Concentrações séricas de retinol de éguas gestantes em haras do Vale do Rio Doce e Sul de Minas Gerais

Abstract: RESUMOForam analisadas as concentrações séricas de retinol de 16 éguas gestantes em haras de duas diferentes regiões de Minas Gerais (Vale do Rio Doce e Sul de Minas). Os animais foram mantidos em pastagens com sal mineral à vontade, sem qualquer suplementação concentrada. Amostras de sangue foram coletadas a cada 30 dias, nos meses de maio a novembro de 2002, objetivando verificar a necessidade de suplementação das éguas com vitamina A nos meses de seca. A concentração de betacaroteno das pastagens também foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Those authors found blood retinol concentration of 6.58 µg/mL, which indicates hypovitaminosis A. In contrast, in Southeastern Brazil, Garcia et al (2006) found no difference (P>0.05) in serum retinol in pregnant mares kept on pasture during the dry season.…”
Section: Resultsmentioning
confidence: 87%
“…Those authors found blood retinol concentration of 6.58 µg/mL, which indicates hypovitaminosis A. In contrast, in Southeastern Brazil, Garcia et al (2006) found no difference (P>0.05) in serum retinol in pregnant mares kept on pasture during the dry season.…”
Section: Resultsmentioning
confidence: 87%